Assessment of the self-care level against COVID-19 and its related factors among hemodialysis patients - Narges Nargesi Khoramabad; Akbar Javadi; Rasool Mohammadi; Atefe Khazaee; Akbar Amiri; Nasrin Moradi; Ronak Garavand (Tehran University of Medical Sciences, 2022)
Background & Aim: Today, COVID-19 has become a serious threat to global health. Due to their certain conditions, hemodialysis patients are more at risk than others. Therefore, self-care in these patients is more necessary. We aimed to assess the self-care of hemodialysis patients against COVID-19 disease and the factors influencing self-care. Methods & Materials: In this cross-sectional study, 219 patients referred to the dialysis ward of selected public hospitals in Lorestan province, were selected by the census method and examined. Patients' information was collected by a demographic questionnaire and a researcher-made questionnaire on self-care against COVID-19. Data were analyzed using the SPSS software version 22, with the significance level of 0.05. Results: The mean score of self-care against COVID-19 in patients was 186.33, and most patients had a good level of self-care. There was a significant relationship between the self-care score and place of residence (P<0.001), and comorbidity (P=0.044). Among the multiple sources of information, there was a significant difference in the self-care score between cyberspace (P=0.047), and family and relatives (P<0.001). Also, comorbidity, urban residence, and academic education level significantly predicted self-care. Conclusion: According to the results of this study, developing proper training programs is suggested considering the factors influencing self-care. Also, capacities such as cyberspace and patients' families should be used to make the training more effective.